2022
DOI: 10.1080/19490976.2021.2018901
|View full text |Cite
|
Sign up to set email alerts
|

Combined exposure to non-antibiotic pharmaceutics and antibiotics in the gut synergistically promote the development of multi-drug-resistance in Escherichia coli

Abstract: The gut microbiota represents an important reservoir of antibiotic-resistant bacteria (ARB), which poses a significant threat to public health. However, little is known about the emergence of ARB in the gut after the combined exposure to antibiotics and non-antibiotic pharmaceutics. Here, Escherichia coli , a common opportunistic pathogen in the gut microbiota, was exposed to the antidepressant duloxetine (2.5 µg/L–25 mg/L) and/or chloramphenicol (6 µg/L–4 mg/L). The resistant strains we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 48 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have revealed that nonantibiotic pharmaceuticals, including fluoxetine and duloxetine, could induce multidrug resistance in E. coli through mutagenesis ( 15 , 16 ). To assess the effects of drug consumption on the horizontal transfer of ARGs in SGF, we used four antidepressants (fluoxetine, amitriptyline, duloxetine, and sertraline) and assessed the conjugative transfer of ARGs between E. coli HB101 and Salmonella Aberdeen in SGF at pH 4.5 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that nonantibiotic pharmaceuticals, including fluoxetine and duloxetine, could induce multidrug resistance in E. coli through mutagenesis ( 15 , 16 ). To assess the effects of drug consumption on the horizontal transfer of ARGs in SGF, we used four antidepressants (fluoxetine, amitriptyline, duloxetine, and sertraline) and assessed the conjugative transfer of ARGs between E. coli HB101 and Salmonella Aberdeen in SGF at pH 4.5 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“… E. coli HB101 containing the RP4 plasmid (60,099 bp) and exhibiting Amp, Kan, and Tet resistance was chosen as the donor. E. coli K-12 exhibiting Chl resistance, obtained from our previous mutation study ( 16 ), and Salmonella Aberdeen exhibiting Str resistance, purchased from the American Type Culture Collection (ATCC 50312), were chosen as the recipients. E. coli HB101 was cultured in Luria-Bertani (LB) medium (Oxoid, UK) containing 100 mg/L Amp, 60 mg/L Kan, and 40 mg/L Tet.…”
Section: Methodsmentioning
confidence: 99%
“…aeruginosa, E. coli, Klebsiella pneumoniae, and Clostridium difficile. , These studies have promoted the importance of drug repurposing for various new applications.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that spontaneously resistant mutants to chloramphenicol were simultaneously resistant to antidepressants due to selection for AcrAB-TolC activity. Recently, the selective serotonin and norepinephrine reuptake inhibitor, duloxetine, and chloramphenicol were reported to impose a selection pressure for marR mutations in E. coli ( 83 ). Thus, there is cross-resistance between antidepressants and antibiotics that may be more wide-spread and suggests that treatment by one class of drug could influence the efficacy of treatment by the other class of drug due to the changes in microbial diversity and associated resistance mechanisms.…”
Section: Discussionmentioning
confidence: 99%